Yargıtay kararları ışığında CIF teslim şekli - Tüfekçioğlu, A. Pınar Altuğ (My University, 2010)
Yargıtay Kararları Işında CIF Teslim Şekli Uluslararası ticaret işlemleri mal ve hizmetlerin bir ülkeden diğerine ihracıyla ilgilidirler. Mallara ilişkin işlemler, uluslararası mal satış sözleşmelerine dayandırılır. İhracat satış işlemleri genellikle ticarî terimlerle şekillendirilirler. Bu terimlerin en çok kullanılanları genel olarak f.a.s., f.o.b. ve c.i.f.’dir. Bu terimler uluslararası ticarî gümrükler tarafından diğer ülkelere mal satışlarının basitleştirilmesi için geliştirilmiştir. Alternatif olarak ihracatçılar, Uluslararası Ticaret Odası tarafından Incoterms adı ile geliştirilen, dilin kolay kullanımı ve kayıtların, ticari terimlerin anlamının tacirler tarafından kolayca, şüpheye kapılmaksızın anlaşılabileceği, bir gurup ticari terimden seçim yapmaktadırlar. CIF (mal bedeli, sigorta, navlun) teslim şekli, diğerlerinden çok daha yaygın ve çok daha sık olarak deniz ticaretinde kullanılmaktadır. Her yıl çok büyük sayıda muamele CIF teslimli sözleşmelere dayalı olarak icra edilmektedir. CIF teslimli sözleşmeler genel olarak malların satışından ziyade malları temsil eden belgelerin satışına ilişkin olarak değerlendirilmektedir. Hukukî bakış açısından CIF teslim şekli, karmaşık durumlara sebebiyet verebilmektedir, zira doğası gereği üç ayrı sözleşmeyi gerektirir: mal satış sözleşmesi, deniz yoluyla taşıma sözleşmesi ve deniz sigortası sözleşmesi. Buna karşın, avantajları nedeniyle uluslararası ticarette en sık kullanılan teslim şeklidir. Tez bu konuları ve CIF teslimli sözleşmeyi; Incoterms, TTK ve Yargıtay Kararları Işığında açıklamayı içermektedir.

CIF Delivery in the Illumination of Supreme Court’s Decisions International trade transactions are relevant to the exportation of goods and services from one country to another. Transactions of goods are based on international sale contracts. Export sales transactions usually embody trade terms. Most common of these terms are f.a.s., f.o.b. and c.i.f. . These trade terms have been developed by international mercantile customs and have simplified the sale of goods abroad. Alternatively, the exporter may choose to make reference in his own conditions of sale to set of standard trade terms for example Incoterms, the trade terms brochure developed by the International Chamber of Commerce under the title of Incoterms, a set of terms developed to eliminate, by the use of plain language, in a register easily understood by traders, any doubts as to the meaning of term. CIF (cost, insurance, freight) is a delivery term which is more widely and more frequently in use than other delivery terms used for purposes of seaborne commerce. An enormous number of transactions is carried out every year under the contracts which has CIF delivery as a clause. CIF delivery is mostly accepted as a delivery type which aim the sale of the documents relevant to goods but not the sale of goods themselves. From the legal point of view, the choice of the c.i.f. term raises complex issues because the c.i.f. transaction embodies, by necessity, elements of three contracts; the contract of sale, the contract of carriage by sea and contract of marine insurance. However, because of its advantages, it is one of the most commonly used delivery term in international trade. The thesis contains this subject and intends to explain the CIF delivery Term in scope of Incoterms, TTK( Turkish Commercial Law ) and Turkey’s Supreme Court’s Decisions.
Keywords: Hukuk; Özel Hukuk